If a*x^3 + b*x^2 + c*x + d is divided by (x - 2), then what is the remainder?

Expert Answers

An illustration of the letter 'A' in a speech bubbles

You need to remember the reminder theorem such that:

`f(x) = (x-2)*q(x) + r(x)`

q(x) and r(x) express the quotient and reminder you'll get after division.

You should substitute 2 for x in equation above such that:

`f(2) = (2-2)*q(2) + r(2)`

Notice that you may evaluate f(2) substituting 2 for x...

See
This Answer Now

Start your subscription to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Start your Subscription

You need to remember the reminder theorem such that:

`f(x) = (x-2)*q(x) + r(x)`

q(x) and r(x) express the quotient and reminder you'll get after division.

You should substitute 2 for x in equation above such that:

`f(2) = (2-2)*q(2) + r(2)`

Notice that you may evaluate f(2) substituting 2 for x in equation of polynomial such that:

`f(2) = 8a + 4b + 2c + d`

You need to substitute`8a + 4b + 2c + d ` for f(2) in equation `f(2) = (2-2)*q(2) + r(2)`  such that:

`8a + 4b + 2c + d = 0*q(2) + r(2)`

`r(2) = 8a + 4b + 2c + d`

Hence, evaluating the reminder r(x) at x=2, under given conditions, yields `r(2) = 8a + 4b + 2c + d` .

Approved by eNotes Editorial Team
An illustration of the letter 'A' in a speech bubbles

The remainder when f(x) = ax^3 + bx^2 + cx + d is divided by x - 2 can be calculated by the remainder theorem. According to this theorem the remainder when a function f(x) is divided by (x - a) is given by f(a)

The required remainer is f(2) = a*2^3 + b*2^2 + c*2 + d

=> 8a + 4b + 2c + d

The remainder of dividing f(x) = ax^3 + bx^2 + cx + d by (x - 2) is 8a + 4b + 2c + d

Approved by eNotes Editorial Team